The feasibility and acceptability of a psychosocial intervention to support people with dementia with Lewy bodies and family care partners. (January 2022) - Killen, Alison; Flynn, Darren; O'Brien, Nicola; Taylor, John-Paul
Objectives: Psychosocial support for people with dementia with Lewy bodies (DLB) and family care partners is frequently lacking, despite the need expressed by those with lived experience. Our objective was to examine the feasibility and acceptability of an intervention designed to build coping capability. Design: The design was non-randomised with all participants receiving the intervention. Setting: The setting was a Memory Assessment and Management Service in the Northeast of England. Participants: Participants comprised 19 dyads consisting of a person with DLB and a family care partner. Intervention: The intervention was group-based, with weekly sessions attended for up to four successive weeks. It was informed by Social Cognitive Theory. Measurements: Data were collected on recruitment, attendance and attrition, self-efficacy, mood, stress and participant experience. Results: Recruitment was achieved with minimal attrition and three successive groups were delivered. Care partners felt more in control and able to cope in at least 3 of 13 areas with 73% feeling this way in eight or more areas. Three themes were identified from post-intervention interviews: people like us, outcomes from being a group member and intervention design. Conclusions: A DLB-specific group intervention is acceptable to people with DLB and family care partners, and recruitment is feasible within a specialist service. Participation may enhance understanding of this condition and reduce social isolation. It may improve care partners' coping capability particularly if targeted towards those with low prior understanding of DLB and more stress. Means of evaluating outcomes for people with DLB need further development.